Calcium looping for pulp and paper industry decarbonisation and hydrogen production from biomass and waste - Da Silva Santos, Monica Patricia (Cranfield University, 2022)
Global CO₂ emissions from fossil fuels have been rising for more than a century. Nevertheless, to meet the ambitious targets set by the Paris Agreement, greenhouse gas emissions must be substantially reduced. The improvement of energy efficiency, implementation of carbon capture and reduction of fossil fuel dependency can play an important role. Of the CO₂ capture technologies, amine scrubbing is the most mature technology; however, calcium looping has shown to be a promising one. Thus, this research aimed to assess the techno-economic feasibility of calcium lopping as a carbon capture technology for combined heat, power and hydrogen production from biomass and/or waste. First, a new concept for the conversion of the pulp and paper industry to carbon-negative that relies on the inherent CO₂ capture capability of the Kraft process was proposed. This concept has shown that a pulp and paper plant can turn from importer to electricity exporter with the cost of CO₂ avoided of 39.0 €/tсо₂ . Second, in the pulp and paper industry, two carbon capture and storage routes were compared, calcium looping retrofitted to the pulp and paper plant and calcium looping coupled with black liquor gasification. The latter was assessed for H₂ production and for electricity generation with a gas turbine combined cycle or solid-oxide fuel cell. The last alternative has shown that the pulp and paper plant can also become a net electricity export asset at the expense of the cost of CO₂ avoided, 50.8 €/tсо₂ . On the contrary, the alternative for H₂ production presented the highest energy penalty but the lowest cost of CO₂ avoided (48.8 €/tсо₂ ). Third, the feasibility of calcium looping for H₂ production and in-situ CO₂ capture was assessed for waste-to-energy conversion in a greenfield scenario. However, this resulted in a significantly higher levelised cost of hydrogen (5.0 €/kgн₂ ) compared to that estimated for conventional gasification (2.7 €/kgн₂ ). Although calcium looping is more cost-efficient for carbon capture in a retrofitted scenario, this technology can become a competitive technology for hydrogen production in a greenfield scenario.
Manovic, Vasilije - Associate Supervisor
Keywords: Calcium looping; carbon capture; sorption-enhanced gasification; techno-economic analysis; waste-to-energy; heat and power capture